Pengaruh Penerapan Green Accounting, Corporate Social Responsibility, Dan Kinerja Lingkungan Terhadap Sustainable Development Pada Perusahaan Manufaktur Sektor Industri Dasar Dan Kimia Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2023 - Dyah Ayu Maudyana (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
The accelerated growth of the industry has resulted in intense competition between companies as they strive to achieve their objectives. This competition exerts a substantial influence on business strategies and the environment, a factor which must be given due consideration in the context of sustainability. Sustainable development is predicated on three fundamental pillars: economic, social and environmental. In order to achieve sustainability, companies must consider the 3Ps (profit, people, planet). The objective of this study was to ascertain and analyse the impact of green accounting, corporate social responsibility, and environmental performance on sustainable development. The research methodology employed a purposive sampling technique, resulting in a sample size of 20 (with five companies over a period of four years). The analysis tool utilises multiple linear regression. The findings indicated that the implementation of a limited form of corporate social responsibility, as defined by the GRI-4 standard, exerts a significant influence on the pursuit of sustainable development. Conversely, the disclosure of green accounting practices, as evidenced by environmental costs and environmental performance metrics derived from PROPER ratings, was found to have no discernible impact on sustainable development. Concurrently, the three independent variables exert an influence on sustainable development.